Ergonomic analysis on wheelchair redesign to improve user health and safety - Kusmindari, Christofora Desi; Pasmawati, Yanti; Arfianto, Ahmad Syahrul; Pratama, Muhammad Rezky Putra; Prassetio, Rendi (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
This research aims to redesign a wheelchair to enhance comfort and safety based on the ergonomic needs of users through a holistic ergonomic approach. The study employs the FMEA (Failure Mode and Effects Analysis) method to identify product failures in wheelchairs and determine preventive measures using the Risk Priority Number (RPN), calculated from Severity (S), Occurrence (O), and Detection (D). A biomechanical assessment using REBA (Rapid Entire Body Assessment) evaluates the posture and movements of wheelchair users and identifies factors contributing to ergonomic risks. The FMEA analysis revealed three failure modes with the highest RPN values: "head drooping" (192), "hands hitting the wheels" (120), and "feet drooping" (112). The REBA assessment indicated a final score of 9, signifying a high risk of injury, necessitating immediate corrective actions. In response to the findings from FMEA and REBA, a new wheelchair design is proposed, incorporating features such as neck support, a hydraulic system for the back, and calf supports. Additionally, the wheelchair dimensions will be adjusted based on the users' anthropometric measurements to ensure better ergonomics.